RESPON PUPUK KANDANG KAMBING DAN PUPUK NPK PADA PERTUMBUHAN DAN HASIL TANAMAN TERUNG HIJAU (Solanum melongena L.). - Yuanita, Visca R; Kurniastuti, Tri; Puspitorini, Palupi (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2016)
Research about influence of goat manure and NPK fertilizer on the growth and yield of green eggplant (Solanum mengolena L.) has been conducted in field village farmer-owned Semen Gandusari District of Blitar which took place in March-April 2016. The aim of this study was to know the interaction for among goat manure and NPK fertilizer on the growth and yield of green eggplant as well as the effect of each factor. This study uses Randomaized Complete Block Design (RCBD) factorial consisting of 16 treatment and each 3 replicates ie: P0M0, P0M1, P0M2, P0M3, P1M0, P1M1, P1M2, P1M3, P2M0, P2M1, P2M2, P2M3, P3M0, P3M1 , P3M2, P3M3. The data taking were plant height, leaf number, fruit length, fruit diameter and weight of fruit per plant. The data were analyzed to F test as followed by a 5% test Honestly Significant Difference (HSD) error level of 5%. The experimental results very significant effect on plant height, leaf number, fruit length and weight of fruits per plant and the effect is not noticeable to the diameter of fruit plants green eggplant. The combined use goat manure 750 g / plant and NPK fertilizer 60 g / plant (P2M3) is proper fertilization to improve the growth and best yield of green eggplant with the highest total weight of the fruit crop that yields 1576.6 grams